Assessing the Impact of Prices Fluctuation on Demand Distortion Within a Multi-echelon Supply Chain - Campuzano Bolarín, Francisco; Guillamón Frutos, Antonio; Lisec, Andrej (Promet - Traffic&Transportation, 2012)
Price fluctuation is a practice commonly used by companies to stimulate demand and a main cause of the Bullwhip effect. Assuming a staggered step demand pattern that responds elastically to retailer’s price fluctuation, and by using a supply chain management dynamic model, we will analyse the impact of these fluctuations on the variability of the orders placed along a traditional multilevel supply chain. Subsequently, the results obtained will serve to propose a forecasting model enabling to calculate the potential variability of orders placed by each echelon on the basis of the price pattern used. Finally, under the hypothesis of an environment of collaboration between the different members of the chain, we propose a predictive model that makes it possible to quantify the distortion of the orders generated by each level. KEYWORDS: Bullwhip effect, systems dynamics, price fluctuation, supply chain management